Cross-border effects of capacity mechanisms in interconnected power systems - Pradyumna C. Bhagwat; Jörn C. Richstein; Emile J.L. Chappin; Kaveri K. Iychettira; Laurens J. De Vries (Utilities Policy, 2017)
The cross-border effects of a capacity market and a strategic reserve in interconnected electricity markets are modeled using an agent-based modeling methodology. Both capacity mechanisms improve the security of supply and reduce consumer costs. Our results indicate that interconnections do not affect the effectiveness of a capacity market, while a strategic reserve is affected negatively. The neighboring zone may free ride on the security of supply provided by the zone implementing a capacity mechanism. However, a capacity market causes crowding out of generators in the energy-only zone. A strategic reserve implemented by this region could aid in mitigating this risk.
Keywords: 330; Capacity market; Cross-border effect; Strategic reserve